2015
DOI: 10.1007/s00425-015-2332-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring natural variation of photosynthetic, primary metabolism and growth parameters in a large panel of Capsicum chinense accessions

Abstract: Collectively, the results presented improve upon the utility of an important genetic resource and attest to a complex genetic basis for differences in both leaf metabolism and fruit morphology between natural populations. Diversity of accessions within the same species provides an alternative method to identify physiological and metabolic traits that have large effects on growth regulation, biomass and fruit production. Here, we investigated physiological and metabolic traits as well as parameters related to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 61 publications
(76 reference statements)
1
9
0
1
Order By: Relevance
“…Capsicum P n values varied more in our experiment (3.6-3.7 to 16.3 mmol CO 2 /m 2 /s fixed) than they did in other experiments reported by others; for example, Ou and Zou (2012) reported that the P n of five Capsicum species varied from 15.8 to 21.8 mmol CO 2 /m 2 /s (fixed). Among pepper varieties within a species, P n also varied more in our experiment than it did in others (Ghasemi et al, 2016;Rosado-Souza et al, 2015). Borisev et al 2012reported that the P n of 10 C. annuum varieties differed from 14.5 to 16.6 mmol CO 2 /m 2 /s (fixed); the C. annuum variety P n (22 varieties) in our work ranged from 3.7 to 16.3 mmol CO 2 /m 2 /s (fixed) ( Table 1).…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Capsicum P n values varied more in our experiment (3.6-3.7 to 16.3 mmol CO 2 /m 2 /s fixed) than they did in other experiments reported by others; for example, Ou and Zou (2012) reported that the P n of five Capsicum species varied from 15.8 to 21.8 mmol CO 2 /m 2 /s (fixed). Among pepper varieties within a species, P n also varied more in our experiment than it did in others (Ghasemi et al, 2016;Rosado-Souza et al, 2015). Borisev et al 2012reported that the P n of 10 C. annuum varieties differed from 14.5 to 16.6 mmol CO 2 /m 2 /s (fixed); the C. annuum variety P n (22 varieties) in our work ranged from 3.7 to 16.3 mmol CO 2 /m 2 /s (fixed) ( Table 1).…”
Section: Discussionmentioning
confidence: 43%
“…P erez-Grajales et al (2004) reported similar P n rates (at a lower irradiance of 500 mmol/m 2 /s) for C. pubescens. Rosado-Souza et al (2015) reported that the C. chinense accession P n varied from 17 to 25 mmol CO 2 /m 2 /s (fixed).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, using this diversity through genetic combinations will allow the emergence of genotypes that are more adapted, productive, and resistant to diseases, among other traits of interest to the market (Souza et al, 2011). Furthermore, it will be possible to differentiate accessions and make them more useful (Padilha et al, 2016a), identifying effective traits in several processes, such as growth regulation, biomass, and fruit production (Souza et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a lot of divergence studies with Capsicum chinense Jacq. described in the literature, such as Finger et al (2010), Faria et al (2012Faria et al ( , 2013, Vasconcelos et al (2014), Souza et al (2015), Padilha et al (2016b) and Pessoa et al (2018), which only evaluate or characterize genetic diversity for the choice of superior parents, none of them evaluates genetic diversity aiming at recommendations for specific market niches. Moreover, studies that aim to observe traits with redundant information for the prediction of genetic diversity are of interest, since it can lead to cost reduction in new experiments.…”
Section: Introductionmentioning
confidence: 99%